2017
DOI: 10.21873/anticanres.11333
|View full text |Cite
|
Sign up to set email alerts
|

Italian Prostate Biopsies Group: 2016 Updated Guidelines Insights

Abstract: These updated guidelines and recommendations are intended to assist physicians and patients in the decision-making regarding when and how to perform a prostatic biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 84 publications
(149 reference statements)
0
13
0
Order By: Relevance
“…To improve PCa detection rate, biopsy of the suspicious area should be performed after mp-MRI of the prostate, even using a simple cognitive fusion technique, based on the observation and localization of prostatic lesions on the MRI image. At least 12 cores should be taken in each patient, in consideration of multifocal entity of PCa 31 .…”
Section: Discussionmentioning
confidence: 99%
“…To improve PCa detection rate, biopsy of the suspicious area should be performed after mp-MRI of the prostate, even using a simple cognitive fusion technique, based on the observation and localization of prostatic lesions on the MRI image. At least 12 cores should be taken in each patient, in consideration of multifocal entity of PCa 31 .…”
Section: Discussionmentioning
confidence: 99%
“…All the biopsies considered in the study were performed with a transrectal approach, as reported in our initial experienceby 3 experienced urologists dedicated to FB (10). Biopsy were performed and specimens collected according to Italian guidelines (11). PCA was considered clinically significant in case of findings of Aim: The upgrading or staging in men with prostate cancer (PCA) undergoing active surveillance (AS), defined as Gleason score (GS) ≥ 3+4 or more than 2 area with cancer, was investigated in our experience using the software-based fusion biopsy (FB) Methods: We selected from our database, composed of 620 biopsies, only men on AS according to criteria of John Hopkins Protocol (T1c, < 3 positive cores, GS = 3+3 = 6).…”
Section: Methodsmentioning
confidence: 99%
“…PSA density and mpMR PSA Densisty (PSAD) is obtained dividing serum total PSA value by prostate volume calculated by imaging (transrectal ultrasound or mpMR) (10). Since 1990, the PSAD enhanced the specificity of cancer detection in men with a normal DRE and an intermediate PSA level (11).…”
Section: Psa Velocitymentioning
confidence: 99%
“…However, it is of outmost importance that a negative MR does not exclude the possibility of significant PCa. Moreover, deciding whether or not is safe to avoid a biopsy in a naïve patient with negative imaging should also rely on PSAD, digital rectal evaluations, nomograms, new biomarkers and family history (10). The PROMIS study showed that the use of mpMRI reduces of a 5% the detection rate of indolent cancers lowering the need of biopsy in 27% of patients (47).…”
Section: The Role Of Mpmrmentioning
confidence: 99%